Sports municipal foundation of valencia user’s profile and their sport practice habits - Ros-Castello, P.; Calabuig Moreno, F.; Gómez Tafalla, A. M. (SPORT TK-EuroAmerican Journal of Sport Sciences, 2019)
The aim of the present study is to analyze the use of the Sports Municipal Foundation of Valencia and to determine its user’s profile. For that purpose 727 online questionnaires were collected, formed by different sections extracted from the existing bibliography. Results show users’ high satisfaction and future intentions. Moreover, users show a greater harmonious passion for sport than compared to the obsessive passion. The most of the sport practice take place form Monday to Friday and after the 19:00h. Facilities users are mainly employed and have university studies. The main use of the facilities is a free and individual use and the main reasons of sport practice are health and wellness.